MANHAJ TAFSIR SUFYAN AL-THAWRY (Dari Madzhab, Muqorin sampai Tartib Ayat) - Muh. Makhrus Ali Ridho (Akademika, 2019)
The author of the book tafsir sufyan al-Thawry is Abū `Abdullāh Sufyān ibn Sa`īd ibnu Masrūq al-Thawry al-Kūfī and also called Abu‘ Abd Allah al-Thawry. The interpretation methodology tafsir sufyan al-Thawry in terms of sources of interpretation, interpretation of Sufyan al-Thawry is included in the category of bi al-ma'thur / bi al-manqul / bi al-riwayah, the source of interpretation is taken from the history of the companions of the Prophet. While in terms of the explanation, the method of interpretation Sufyan al-Thawry falls into the category of muqarin method. While in terms of the extent of the explanation, the interpretation of Sufyan al-Thawry belongs to the interpretation which uses the ijmali interpretation method. While in terms of the objectives and order of the interpreted verse, the interpretation of Sufyan al-Thawry falls into the category of interpretation using the tahlili method, because Imam Sufyan al-Thawry interprets the verse in accordance with the order of the Ottoman Manuscripts beginning with al-Fatihah until the letter an-Nass. Regarding al-ittijah / al-naz'ah or the tendency of Sufyan al-Thawry interpretation written by Imam Sufyan al-Thawry, the writer classifies this interpretation in the category of interpretation which has al-ittijah lughawi / adaby and fiqh.